THE EFFECTIVENESS OF THE COMBINATION SNAKEHEAD FISH AND MORINGA LEAVES ON INCREASING HEMOGLOBIN LEVELS IN PREGNANT WOMEN WITH ANEMIA - Ummah, Wiqodatul; Putri, Santy Irene; Utami, Woro Tri (LPPM Universitas Duta Bangsa Surakarta, 2025)
Maternal anemia remains a major public health problem, particularly in developing countries, including Indonesia. Conventional iron supplementation often faces adherence issues due to side effects, thus highlighting the need for alternative, food-based interventions utilizing locally available resources. Snakehead fish (Channa striata) is rich in high-quality protein, albumin, and bioavailable iron, while moringa leaves (Moringa oleifera) contain plant-based iron, vitamin C, and antioxidants that enhance iron absorption. This study aimed to evaluate the effectiveness of floss products based on snakehead fish and moringa leaves to increase hemoglobin levels in pregnant women with anemia. A quasi-experimental study was conducted on 40 pregnant women with anemia, divided into one control group (floss products without moringa) and one intervention groups with different moringa additions every week (15 g, 20 g, and 25 g). Each participant consumed 150 g of floss products daily for 3 weeks. Hemoglobin levels were measured before and after intervention using standard procedures. Data were analyzed using the Wilcoxon Signed Rank Test and Mann-Whitney U Test with a 95% confidence level. The mean hemoglobin level increased from 9.7 g/dL (SD = 0.3) to 10.6 g/dL (SD = 0.5) after the intervention (p < 0.001). The intervention groups achieved significantly higher hemoglobin levels (mean = 12.5 g/dL, SD = 0.9) compared to the control group (mean = 11.2 g/dL, SD = 0.7), with p = 0.002. The combination of snakehead fish and moringa leaves was effective in improving hemoglobin levels among pregnant women with anemia.